Avian influenza mRNA vaccine encoding hemagglutinin provides complete protection against divergent H5N1 viruses in specific-pathogen-free chickens - Zhaoyang Wang; Chongyu Tian; Jiahang Zhu; Shiqian Wang; Xiang Ao; Yanjuan He; Huixin Chen; Xiuying Liao; Deming Kong; Yongfei Zhou; Wanbo Tai; Ming Liao; et al. (Journal of Nanobiotechnology)
Abstract Background The rapid mutation of avian influenza virus (AIV) poses a significant threat to both the poultry industry and public health. Herein, we have successfully developed an mRNA-LNPs candidate vaccine for H5 subtype highly pathogenic avian influenza and evaluated its immunogenicity and protective efficacy. Results In experiments on BALB/c mice, the vaccine candidate elicited strong humoral and a certain cellular immune responses and protected mice from the heterologous AIV challenge. Antibody and splenocyte passive transfer assays in mice suggested that antibodies played a crucial role in providing protection. Experiments involving SPF chickens have revealed that two doses of the 5 µg vaccine candidate in this study provided 100% complete protection against homologous strains, but only 50% complete protection against heterologous strains. Even immunization with two doses of the 15 µg vaccine candidate resulted in 90% complete protection against heterologous strains. To enhance the immune efficacy of the candidate vaccine, we designed 6 sequences with different secondary structures and screened out the candidate sequence with the highest expression (SY2-HA mRNA). Experiments on SPF chickens showed that two doses of 5 µg SY2-HA mRNA-LNP vaccine provided 100% complete protection against homologous and heterologous H5N1 AIV strains. Immunization tests with the SY2-HA mRNA-LNP vaccine were repeated in the SPF chicken model, inducing antibody production levels that are consistent with previous tests and providing 100% complete protection against both homologous and heterologous strains of the virus, indicating that the vaccine has a stable immune efficacy. Conclusions The vaccine developed in this study provides complete protection against divergent H5N1 AIV strains in chickens, offering a promising approach for the future development of mRNA vaccines against multivalent avian influenza subtypes. Graphical Abstract